Chemical analyses of glass beads from two Early Iron Age sites in Zimbabwe: Zhizo Hill and Makuru. Issue 3 (3rd July 2018) - Wilmsen, Edwin; Dussubieux, Laure; Huffman, Thomas; Wood, Marilee
ABSTRACT: Glass beads from the East African coast obtained through the Indian Ocean trade have been known for a half-century to have been taken into the interior of southern Africa. Zhizo Hill and Makuru, both situated in central Zimbabwe, were among the first Early Iron Age sites where such beads were recovered. Zhizo Hill subsequently became the name site for these beads and associated pottery, now called Zhizo. Makuru was among the very few mid-twentieth century sites with adequate charcoal from which the first radiocarbon dates associated with Zhizo beads and ceramics were obtained. Yet the beads from neither site have been analysed before this nor described in any adequate way. This paper presents the results of their analyses by Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry along with reassessments of those first radiocarbon dates. It then considers the implications of these data and the complexities of interpretation regarding the beads in southern Africa still to be addressed.